The Nexus between Green Banking Initiatives and Environmental Performance: Examining the Moderating Effect of Environmental Risk Management - HOANG, Vu Hiep,; NGO, Quoc Dung,; NGUYEN, Dang Tuan,; HO, Hoang Ha, (Journal of Ecohumanism, 2024)
This study investigates the relationships among green banking initiatives, green innovation, environmental risk management, and environmental performance in the Vietnamese banking industry. The research model is developed based on the existing literature and tested using structural equation modeling (SEM) on a sample of 459 mid-level managers from 36 banks in Vietnam. The findings reveal that green lending, green investment, and green internal operations have significant positive effects on green innovation, which in turn has a significant positive effect on environmental performance. Moreover, environmental risk management positively moderates the effects of green banking initiatives on green innovation, as well as the effect of green innovation on environmental performance. The robustness tests, including alternative model specification, subgroup comparisons, control variable analyses, and triangulation with secondary data and literature, provide consistent and complementary evidence for the hypothesized relationships. The study makes several important contributions to the literature on green banking, sustainability, and innovation in Vietnam. It develops and tests a comprehensive theoretical model, uses a large sample of mid-level managers from multiple banks, employs rigorous statistical methods and robustness tests, and highlights the critical role of environmental risk management in the effective implementation of green banking and innovation strategies. The findings offer valuable insights and practical implications for bank managers, regulators, and policymakers in Vietnam, as the country strives to promote sustainable finance and address pressing environmental challenges.